M. Lipsky (1980), Street-Level Bureaucracy: The Dilemmas of the Individual in Public Service, Russell Sage Foundation, New York. - Βλασσόπουλος Γιάννης (Κοινωνική Πολιτική, 2018)
Δε διατίθεται περίληψη